Job satisfaction and organizational commitment among Catholic primary school teachers of Merauke - Berlinda Setyo Yunarti; Mozes M. Wullur; Basilius Redan Werang (Intelektual Pustaka Media Utama, 2020)
A high rate of teacher absenteeism in Merauke regency, Papua Province, Indonesia might be attributed to the low commitment of primary school teachers to educate the young people of Merauke, Indonesia. This study aimed to examine whether a positive and significant correlation exists between the organizational commitment and job satisfaction of the Catholic primary school teachers of Merauke, Indonesia. Applying a survey approach, two quantitative survey forms were distributed to a total of 157 teachers working in the Catholic primary schools of Merauke, Indonesia. A face-toface way of data collection was employed by having a prior consent from all the informants personally. Using Pearson’s correlation analysis as a tool for analyzing the collected data, the study showed a positive and significant correlation among the two surveyed variables as the amount of Pearson’s correlation coefficient (R) is .875 and the probability coefficient (ρ) is .000. The major conclusion of this study is that the job satisfaction and organizational commitment of the Catholic primary school teachers of Merauke, Indonesia, are significantly positively correlated. Practical implication of the finding is that the need for the school principals to promote the organizational commitment of teachers by enhancing their job satisfaction in order that the Catholic primary school students’ right to be well educated would be addressed adequately. Despite the possibility of the similar conclusion of this study with the previous studies conducting in other countries, the finding may support the current knowledge on the topic by giving a valuable information from an empirical context of Merauke, Indonesia.